2018
DOI: 10.15561/20755279.2018.0303
|View full text |Cite
|
Sign up to set email alerts
|

The influence of cheerleading exercises on the demonstration of strength and endurance of 15-17-year-olds girls

Abstract: to define dynamics of indicators of endurance and strength development of 15-17-year-olds girl-students after application of cheerleading exercises.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 20 publications
0
12
0
1
Order By: Relevance
“…The range of indices reflecting physical fitness and adaptive capacity was applied to assess the dynamics of physical health under the influence of a multi-level system of differentiated education (Masliak & Mameshina, 2018). Krivoruchko, Masliak, Bala, Skripka and Honcharenko (2018) applied the physical development indices as a criterion for the effectiveness of training in cheerleading.…”
Section: Discussionmentioning
confidence: 99%
“…The range of indices reflecting physical fitness and adaptive capacity was applied to assess the dynamics of physical health under the influence of a multi-level system of differentiated education (Masliak & Mameshina, 2018). Krivoruchko, Masliak, Bala, Skripka and Honcharenko (2018) applied the physical development indices as a criterion for the effectiveness of training in cheerleading.…”
Section: Discussionmentioning
confidence: 99%
“…The above is confirmed by the data of (Adel et al, 2019;Mokhtar et al, 2019;Saddek et al, 2020), according to which it was found that during physical exertion, muscle hypertrophy occurs as a result of adaptive-trophic influence (Mukund & Subramaniam, 2020;Teplov, 1982), which is characterized by an increase in thickness and denser packaging of contractile elements of muscle fiber (Haun et al, 2019;Narici et al, 1996). Thus, studies (Annesi, Westcott, Faigenbaum, & Unruh, 2005;Belkadi et al, 2019;Krivoruchko et al, 2018;I. P. Masliak & Mameshina, 2018) indicate that the introduction of functional exercises in the main part of the lesson contributed to a significant improvement in strength abilities of high school students.…”
Section: Discussionmentioning
confidence: 65%
“…P. Masliak & Mameshina, 2018;Petrova & Bala, 2020) note that according to statistics, almost 60% high school children have health problems and low levels of physical fitness. The main reasons for this problem are the features of education in the modern school (Krivoruchko, Masliak, Bala, Skripka, & Honcharenko, 2018), the growth of educational information, the intensification of material, modernization and complication of educational programs (Varea, Riccetti, & Siracusa, 2021). All this leads to an increase in mental load and a decrease in motor activity of children (Batorova & Sørensen, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Саме фізична підготовка має провідне значення у структурі багаторічного спортивного удосконалення спортсменів у стрільбі з лука [4,6,7]. Поряд з цим, зміст і структура тренувального процесу стрільців з лука під час навчання у ВНЗ недостатньо досліджені.…”
unclassified